UPAYA PENCEGAHAN STUNTING MELALUI PROGRAM ‘PRAGATI: PENDIDIKAN REPRODUKSI DAN GIZI TERINTEGRASI’ UNTUK REMAJA - Sutami, Irma Ayu; Rahayu, Siti; Iva Prestiana, Novita Dian; Qintharah, Yuha Nadhirah (Universitas Islam 45 Bekasi, 2024)
Stunting is a condition where toddlers can show stunted growth compared to their age and height. Acceleration of stunting reduction from current conditions is needed to ensure the achievement of the stunting prevalence target set by the World Health Assembly (WHA), which is to reduce stunting rates by 40% from the 2013 prevalence of 22% in 2025, and the Sustainable Development Goals (TPB) which is to eliminate all forms of malnutrition by 2030. One of the keys to health development is reducing the prevalence of stunting in children. Children who have a history of stunting can experience physiological disorders, one of which is during adolescence. However, not all people know the physiological impacts of stunting that are felt during adolescence. For this reason, socialization was held regarding efforts to prevent stunting through the PRAGATI program: 'Integrated Reproductive and Nutrition Education' for adolescents. The purpose of this service is to provide education to adolescent girls about stunting. The implementation method uses community education. The results of this community service have a significant impact in several aspects. The program has successfully increased the knowledge of grade 12 students about stunting, reproductive health, and the importance of balanced nutrition. This improvement can be an important asset for students in maintaining their health and preventing stunting in the future.